Contractile properties and fatigue of the diaphragm in man. Issue 3 (March 1981) - Moxham, J; Morris, A J; Spiro, S G; Edwards, R H; Green, M
Abstract : We studied the pressure developed by the diaphragm in response to stimulation of the phrenic nerve in the neck, in three normal men. When the phrenic was electrically stimulated at increasing frequencies the diaphragm responded by increasing transdiaphragmatic pressure to give a frequency-pressure curve similar to the frequency-force curve for other skeletal muscles. The subjects than breathed through an inspiratory resistance for as long as possible and the frequency-pressure curve was repeated. It was found that the diaphragm developed low frequency fatigue, in the same way as previously described for other muscles. We conclude that the diaphragm has contractile properties similar to these of other skeletal muscles. Low frequency fatigue of the diaphragm could contribute to respiratory failure in patients with lung disease.